System for wind and waves measurement on the lake - Gierusz, W.; Rak, A.; Sikora, P. (Scientific Journal of Gdynia Maritime University, 2017)
The paper describes the measurement system of wind and waves on the lake. Wind speed, direction and waves height are measured in order to build simulation model of environmental disturbances of the ship model control process on the lake. Two ultrasonic anemometers were installed in the unit along with the originally designed system for measurement of the wave height. The first exemplary results recorded on the lake are presented at the end of the paper.